LEGAL ANALYSIS OF ARMED SEPARATIST CONFLICTS CARRIED OUT BY THE FREE PAPUA ORGANIZATION FROM THE PERSPECTIVE OF LAW NUMBER 5 OF 2018 CONCERNING THE ERADICATION OF CRIMES OF TERRORISM - Eko Bayu Saputra; Mukidi Mukidi; Indra Gunawan Purba (LPPM YPITI, 2026)
Armed Separatist Group (KSB) The Free Papua Organization (OPM) considers this group to be fighters trying to separate themselves from Indonesia. A series of attacks by the KKB/KSB/OPM against security forces in Papua prompted the government to designate such acts of violence as a criminal act of terrorism. The phenomenon of armed separatist conflict carried out by the Free Papua Organization in the perspective of Law Number 5 of 2018 concerning the Eradication of Terrorism Crimes is that OPM, which is a separatist movement, often commits violent acts that are categorized as terrorism, especially if the act meets the elements regulated in the Law. The designation of OPM as a terrorist organization has significant legal implications, including the application of criminal sanctions for terrorism for its members.